The threat of “soulful pornography” in cloud computing and metaverse thinking : Toward a panentheistic theology of diachronic thinking in pastoral caregiving - Louw, Daniël (Stellenbosch Theological Journal, 2024)
Due to the impact of metaverse thinking, both religious thinking (homo religiosus) and the spirituality of transcendence (homo transendentalis) is constantly exposed to the demands of what can be called a digitalized online spirituality (homo digitalis). Facebook and Instagram brought about a fundamental paradigm change regarding spiritual experiences. It transformed the spirituality of metaphysical and analytical thinking into diachronic networking: I am digitalised, therefore I am. I start to exist through and via (Greek: dia) the digitalized other. Thus, the following research question in pastoral theology: If the traditional understanding of “God” as an all-controlling and all-powerful deity, is challenged by the multidimensionality of metaverse cosmology and optimized anthropology, how should orthodox and traditional faith be reframed and rephrased to still care to the existential needs of human beings surfing the internet within cyberspatiality? Caregiving is constantly being challenged by the following existential predicament of homo digitalis: The lurking danger of digital disillusions (the dystopia of a “messianism of networking digitalism”, Han 2012:6). The following pastoral question surfaces: What about the soulful needs of the human spirit? Especially, when vulnerable and wounded human beings become exposed to irreparable loss and the unavoidable factuality of fatal mortality? It is argued that metacene thinking should be supplemented by a kind of caring Space-praxis (cura pro spacio). The pastoral challenge is to start focussing on the cure and care of disillusioned netizens. In this regard, a “pneumatology of diachronic panentheism” is proposed.